2022
DOI: 10.24028/gj.v44i2.256264
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic prospecting and rock magnetic study of soils and archaeological objects on the Late Roman time sites near Komariv in Middle Transnistria

Abstract: The paper presents the outcome of the magnetic survey at the settlement and cemetery of the production center of the 3rd—5th centuries, Komariv (Khotyn district, Chernivtsi region), which is located on the right bank of the Dniester. The settlement has about seventy anomalies that may have an archaeological origin. The archaeological study of individual anomalies has confirmed, as expected, the reliability of geophysical interpretation of thermal structures (kilns, furnaces) and living and production dugouts d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…If such third party material is not under the Creative Commons license, any copying, editing or public reproduction is only permitted with the prior consent of the respective copyright owner or on the basis of relevant legal authorization regulations. It was demonstrated that neither a magnetometer survey nor a GPR survey is able to resolve all the archaeological issues on the sites of the region (Bondar et al 2022a).…”
Section: Proceedings Of the 15th International Conference On Archaeol...mentioning
confidence: 99%
“…If such third party material is not under the Creative Commons license, any copying, editing or public reproduction is only permitted with the prior consent of the respective copyright owner or on the basis of relevant legal authorization regulations. It was demonstrated that neither a magnetometer survey nor a GPR survey is able to resolve all the archaeological issues on the sites of the region (Bondar et al 2022a).…”
Section: Proceedings Of the 15th International Conference On Archaeol...mentioning
confidence: 99%
“…The paper represents an attempt to assemble relevant evidence from magnetometer and ground penetrating radar (GPR) surveys, remote sensing and geospatial investigations, results of limited archaeological excavations to recognize Roman structures on the Buzovytsia-1 settlement recently discovered in Chernivtsi region (Ukraine). It was demonstrated that neither a magnetometer survey nor a GPR survey is able to resolve all the archaeological issues on the sites of the region (Bondar et al 2022a). Challenging conditions for magnetometry are represented by the use of limestone as a building material for Roman structures, and for GPR by high clay content in the soil causing adsorption of electromagnetic waves, and thus providing poor depth for GPR exploration.…”
Section: Introductionmentioning
confidence: 99%